Reconceptualizing authenticity in islamic urban heritage: A critical spatial analysis of ritual practice, collective memory, and community engagement - Yulistyoningsih, Maya; Mehmet A.K.; Ayako, Awa Salma (The Journal of City: Branding and Authenticity, 2025)
Background: Eyüpsultan, one of Istanbul’s most historically and spiritually significant Islamic urban quarters, faces increasing pressure from rapid urban development and heritage commodification. These transformations challenge conventional understandings of authenticity, especially in sacred urban contexts. This study aims to introduce and develop the concept of Lived Authenticity—a framework that interprets authenticity not only as material preservation but as a dynamic, culturally embedded experience shaped by ritual, spatial memory, and community engagement. Methods: Using a qualitative methodology, the research combines visual-spatial ethnography, photographic documentation, semi-structured interviews, and historical-architectural review conducted over a twelve-month period in Eyüpsultan. Findings: The study finds that the authenticity of Eyüpsultan is continuously produced and reaffirmed through embodied religious practices, evolving spatial configurations, and collective memory. This Lived Authenticity resists static or object-based definitions, offering instead a perspective rooted in continuity of use and sacred urban rhythms. Conclusion: The research challenges dominant conservation paradigms by proposing a contextually grounded model of authenticity, contributing to theoretical discourses in Islamic urban heritage and offering insights for participatory, community-oriented preservation strategies. Novelty/Originality of this Article: This study offers a novel concept of “Lived Authenticity” that reconceptualizes urban heritage authenticity as an active, embodied cultural experience shaped by community practices and spatial memory, moving beyond traditional static preservation models.